PUBLIC MECHANISMS OF INNOVATION DEVELOPMENT AS A FACTOR OF ENSURING ECONOMIC SECURITY OF UKRAINE - Verbytska, H. L. (The actual problems of regional economy development, 2024)
The article is aimed at studying the problems of development of innovation activity of enterprises and formation of public mechanisms for its activation to ensure economic security of Ukraine. The main objectives of the study are to analyse the current state of innovation activity of domestic enterprises, determine the impact of innovation activity on the economic security of Ukraine; develop public mechanisms for the development of innovation activity in Ukraine. The article uses such scientific methods as analysis, synthesis, comparison, induction, deduction, analytical and structural-logical. The results of the study show that the Russian military aggression has had a negative impact on the pace of innovation by domestic enterprises, moreover, it has put entire industries on the brink of survival. It has been established that the main share of Ukraine's exports is made up of agricultural products, which does not contribute to the development of intellectual potential and leads to a decrease in the economic security of the State. The existing approaches to defining the essence of the concept of "economic security" do not fully take into account the role of innovations in its provision. It is proposed to understand economic security as the ability of a country in the context of globalisation and competition to ensure the stability and efficiency of its economy, making maximum use of all available economic potential, protecting its own economic interests from external threats, by developing innovation and ensuring social stability. It is proved that intensification of innovation activities of enterprises can ensure GDP growth, increase the level of welfare of the population, which will contribute to sustainable economic development and social stability. The role of public administration in stimulating the innovation activity of enterprises is determined. The scientific novelty of the study lies in the use of an integrated approach to substantiating public mechanisms for the development of innovation activity. At the same time, the efforts of public authorities should be focused on supporting innovative enterprises to overcome the technological gap with developed countries. It is important that public mechanisms for innovation development are targeted, efficient, transparent and flexible. They should be aimed at supporting priority areas of economic development, ensure maximum return on investment, be understandable and accessible to all businesses, and be able to adapt to changing market conditions.